Skeletal Manifestations in Acute Lymphoblastic Leukaemia - Begum, Mahmuda; Fatmi, LE; Islam, Khandaker Tarequl; Mehnaz, Syeda; Huda, SM Shamsul; Rahman, Farhana (Bangladesh Journal of Child Health, 2019)
Background: Skeletal manifestations associated with ALL in children are common findings with a high prevalence (11.6 to 50%). The most common skeletal manifestations are bone pain, arthritis, failure to use an extremity as well as other complaints mimicking orthopedic condition such as osteomyelitis. The objective of this study is to determine the rate of skeletal manifestations commonly present in ALL to reduce mortality and morbidity. Methods: This cross-sectional study was carried out in the department of Pediatrics in Dhaka medical college Hospital, BSMMU and Dhaka Shishu (Children) Hospital between January 2010 to July 2010. Total Fifty patients of ALL were Selected consecutively from the study population. At first, we assessed skeletal manifestations like bone pain, arthritis, radiological findings present or not in ALL. Then specify the rate of bone pain, arthritis, radiological findings of ALL patients. Results: After six months 35 patients were present with skeletal manifestations. Among them 20 patients, presented with bone pain,10 patients presented with arthritis and 5 patients presented with radiological manifestations. Out of 5 patients 3 patients had soft tissue swelling 1 patient had periarticular osteoporosis and 1 patient had joint effusion in x-ray findings. Conclusion: Skeletal manifestations may be the only presentation in ALL. Bangladesh J Child Health 2019; VOL 43 (2) :102-105